The Effect of Ownership and Regulation on Bank Earnings Quality an investigation of the conventional and Islamic banks in MENA region - Bourkhis, Khawla; Najar, Mohamed Wajdi (European Journal of Islamic Finance, 2017)
The study aims to examine the relationship between shareholding ownership structures, national institutional factors and earnings quality of banks across MENA countries (Middle East and North Africa). Using four distinct earnings quality measures that detect different aspects of earnings properties on a sample of 158 banks (44 Islamic banks and 114 conventional banks), the study finds that all four measures of earnings quality are higher for listed and widely held banks; and, that state-owned banks have less persistent, less predictable, and less managed earnings. Moreover, Islamic banks in MENA countries appear to have significantly higher quality of earnings than their conventional counterparts in terms of earnings persistence, cash-flows predictability and income smoothing using loan loss provisions. The study shows also that tighter supervision improves earnings reporting quality by reducing earnings management practices even in the presence of large shareholding.